Perbaikan Instalasi dan Pemasangan Lampu Penerangan Masjid Kampung Kiat, Distrik Fakfak Barat - Rusliadi Rusliadi (Edumedia Solution, 2022)
Electrical installation is one way to distribute electricity from the generating center to the load center. The occurrence of fires due to electricity can be caused by several things, including installations that are not in accordance with PUIL standards, irregular maintenance and the use of sockets that accumulate. This is what encourages lecturers and students of the electrical engineering study program at the Fakfak State Polytechnic to carry out a service to repair the installation and installation of mosque lighting in the village of Tips, West Fakfak district. Based on the results of this service, electrical installations have been repaired in accordance with the provisions of the PUIL standard, followed by the installation of lighting on the terraces and prayer rooms. The mosque terrace lighting only uses one switch. This aims to make it easier when turning on the mosque terrace lights.